The Infinity courts - Bowman, Akemi Dawn (Simon & Schuster BFYR, 2022)
Murdered on the way to her high school graduation party, eighteen-year-old Nami Miyamoto finds herself in an afterlife ruled by Ophelia, a virtual assistant planning to eradicate human existence.